2019
DOI: 10.1002/bjs.11243
|View full text |Cite
|
Sign up to set email alerts
|

Qualitative study of clinician and patient perspectives on the mode of anaesthesia for emergency surgery

Abstract: Background Although delivering a chosen mode of anaesthesia for certain emergency surgery procedures is potentially beneficial to patients, it is a complex intervention to evaluate. This qualitative study explored clinician and patient perspectives about mode of anaesthesia for emergency surgery. Methods Snowball sampling was used to recruit participants from eight National Health Service Trusts that cover the following three emergency surgery settings: ruptured abdominal aortic aneurysms, hip fractures and in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 24 publications
2
6
0
Order By: Relevance
“…The range of factors identified as shaping choice of anaesthesia modality demonstrates the complexity of anaesthesia as an intervention and that the choice of mode of anaesthesia is determined by several interlinking factors that include not just the anaesthetist, but also the patient and surgeon. This concurs with a recently published qualitative study of clinician and patient perspectives on the mode of anaesthesia by Dooley et al., which also demonstrated that decisions about the mode of anaesthesia depend upon several interlinking factors, including expertise, preference, habit, practicalities and norms . This also showed variation in practice in choosing modes of anaesthesia and significant uncertainty regarding the effects of different anaesthesia types on post‐operative outcomes .…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…The range of factors identified as shaping choice of anaesthesia modality demonstrates the complexity of anaesthesia as an intervention and that the choice of mode of anaesthesia is determined by several interlinking factors that include not just the anaesthetist, but also the patient and surgeon. This concurs with a recently published qualitative study of clinician and patient perspectives on the mode of anaesthesia by Dooley et al., which also demonstrated that decisions about the mode of anaesthesia depend upon several interlinking factors, including expertise, preference, habit, practicalities and norms . This also showed variation in practice in choosing modes of anaesthesia and significant uncertainty regarding the effects of different anaesthesia types on post‐operative outcomes .…”
Section: Discussionsupporting
confidence: 90%
“…This concurs with a recently published qualitative study of clinician and patient perspectives on the mode of anaesthesia by Dooley et al., which also demonstrated that decisions about the mode of anaesthesia depend upon several interlinking factors, including expertise, preference, habit, practicalities and norms . This also showed variation in practice in choosing modes of anaesthesia and significant uncertainty regarding the effects of different anaesthesia types on post‐operative outcomes .…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Clinician autonomy is acknowledged as a necessity in anaesthesia and is a fundamental reason for variation in practice. There is emerging evidence that the choice of mode of anaesthesia (GA, local anaesthesia, regional or sedation) is multifactorial, formulated around clinicians’ expertise, preference, habit, policies, practicalities and may also be influenced by other healthcare professionals and patients 4. While the autonomous nature of anaesthesia is partly unavoidable, the lack of standardisation and consistency in how anaesthetic techniques are defined, administered and reported complicates the interpretation of published evidence and planning of future RCTs 1 5…”
Section: Introductionmentioning
confidence: 99%
“…On 23 January, @bjsurgery held a joint tweetchat with @Anaes_Journal and the co‐authors of four papers on emergency surgery in the joint special issue. This generated over 8 million impressions for the tweetchat hashtag #BJSConnect, an increase from the previous BJS tweetchat impression count of 5 million.…”
mentioning
confidence: 99%